ATLAS OTALEX C - Cáceres, Carmen Caballero (2014)
Extremadura, in Spain, and Alentejo and Centro, in Portugal, are tree regions belonging to different countries but with several common interests. They are continuous border areas that share similar ecological, socioeconomic and environmental characteristics. The cooperation between these territories which promotes the collaboration and exchange of information between both sides of the Spanish-Portuguese frontier, has important references in several crossborder projects, such as: COORDSIG “Coordination of Geographical Information Systems and Instruments of Territorial Observation in Low Density Rural Areas”, co-financed by EFRD, program Interreg II C, developed between 1997 and 2001; PLANEXAL “Territorial Recognition for the approach of common urban-territorial management and planning strategies in Extremadura and Alentejo”, co-financed by Interreg III A Spain Portugal Program, between 2003 and 2005; GEOALEX “Geographical model for environmental and territorial management of rural low density areas”, co-financed by Interreg III A (Sub-program Alentejo-Extremadura) from 2004 to 2006; OTALEX “Territorial Observatory Alentejo Extremadura”, co-financed by Interreg III A Spain-Portugal Program, developed from 2006 to 2009; and OTALEX II “Territorial and Environmental Observatory Alentejo Extremadura”, co-financed also by Interreg III A Spain-Portugal Program and developed between 2008 and 2011. Starting in 2009 as the ongoing project of OTALEX II, OTALEX C “Territorial and Environmental Observatory Alentejo Extremadura Centro”, co-financed by the Cross Border Cooperation Operational Program of Spain-Portugal 2007-2013 (POCTEP), has as main purpose the creation of a management and environmental monitoring system thought the SDI – IDE OTALEX (Spatial data infrastructure of the Territorial and Environmental Observatory Alentejo-Extremadura-Centro - www.ideotalex.eu) as an information and institutional sharing platform between Alentejo-Extremadura-Centro administrations. The project is integrated by different spanish and portuguese entities that belong to three levels of administration. At national level the spanish Nacional Centro of Geographical Information / Nacional Geographical Institute (CNIG-IGN) and portuguese General Territory Direction (DGT); at the regional level, the General Direction for Transports, Territorial Management and Urbanism (Consejería of Fomento, Vivienda, Territorial Management and Tourism – Government of Extremadura) and Coordination and Regional Development Commission of Alentejo (CCDR-A); at local level, Intermunicipal Community of Central Alentejo (CIMAC), Intermunicipal Community of Alto Alentejo (CIMAA), O. A. Equality and Local Development Area (Diputación of Badajoz) and Diputación of Cáceres; in the high education, the University of Extremadura, the University of Évora and the Polytechnic Institute of Castelo Branco; and as public enterprise, the Enterprise of Development and Infra-structures of Alqueva Dam, S.A. (EDIA). The publication of this crossborder atlas of Alentejo-Extremadura-Centro regions, the ATLAS OTALEX C, integrates the results of an extensive series of crossborder projects overcoming the fruitful cohesion of territories in the defence of their common interests. The present publication collects and synthetizes the harmonization effort made in bringing in common the information of the distinct partners of OTALEX C project, and aims to contribute in an effective way to the sustainable development of these crossborder regions through the definition of common strategies and of the implementation of crossborder of territorial and environmental observation instruments.